MANAGEMENT OF RESOURCE AND INFORMATION FLOWS IN INDUSTRIAL ENTERPRISES: CHALLENGES AND SOLUTIONS - LYSAK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the pressing issues of managing resource and information flows in industrial enterprises in the context of global competition, rapid technological advancements, and digital transformation. The author focuses on the issues and challenges of fragmented information systems, low integration levels, the difficulties of introducing modern technologies into outdated infrastructure, and insufficient automation of key processes. Special attention is given to optimizing resource utilization, enhancing management flexibility, achieving accurate forecasting and planning, and implementing advanced digital management tools.The author proposes solutions to these challenges, including the adoption of ERP systems, Internet of Things (IoT) technologies, Big Data analytics, artificial intelligence, and cloud platforms. The importance of creating unified information sources, integrating existing information systems through application programming interfaces (APIs), enhancing cybersecurity, and adapting personnel to new technologies and changes in management processes is emphasized. The paper details the benefits of digitalization, such as cost reduction, improved production efficiency, increased flexibility, and rapid adaptation to changing market conditions.The research findings demonstrate that integrating modern technologies into production and management processes allows enterprises not only to respond effectively to changes but also to ensure high competitiveness through the optimization of resources and information flows. The article identifies promising directions for implementing innovative solutions, including the development of artificial intelligence technologies for forecasting, adaptive logistics systems, advanced monitoring tools, and automation, which contribute to improving product quality and operational efficiency.The conclusions provide recommendations for industrial enterprises on adopting digital technologies, automation, and the integration of information systems to achieve effective resource and information flow management. Emphasis is placed on the importance of a phased approach to implementing digital tools, staff training, and maintaining robust cybersecurity. The recommendations also include the use of cloud platforms and data exchange standards to optimize costs, enhance decision-making efficiency, and ensure the sustainable development of industrial enterprises.
Keywords: industrial enterprise management; integration of information flows; optimization of resource flows; management digitalization; smart manufacturing; industrial Internet of Things (IIoT); Big Data; ERP systems